2023
DOI: 10.1007/s13538-023-01259-z
|View full text |Cite
|
Sign up to set email alerts
|

The Bulk Flow Motion and the Hubble-Lemaître Law in the Local Universe with the ALFALFA Survey

Abstract: The bulk flow motion and the Hubble-Lemaître law in the Local Universe flow on the structures of the Local Universe which manifests through a dipolar behavior of the Hubble constant in opposite hemispheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…For the survey configuration we adopt the same parameters used in ref. [1] to reproduce the ALFALFA catalogue footprint, that is, the HI line emission survey of extragalactic sources in the Local Universe [55][56][57][58][59][60][61][62][63]. The survey covers two discontinuous regions on the sky, both in the declination range of 0 • < DEC < 36 • , in the right ascension intervals of 21 h 30 m < RA < 3 h 15 m (South galactic hemisphere) and 7 h 20 m < RA < 16 h 40 m (North galactic hemisphere).…”
Section: Log-normal Simulated Cataloguesmentioning
confidence: 99%
“…For the survey configuration we adopt the same parameters used in ref. [1] to reproduce the ALFALFA catalogue footprint, that is, the HI line emission survey of extragalactic sources in the Local Universe [55][56][57][58][59][60][61][62][63]. The survey covers two discontinuous regions on the sky, both in the declination range of 0 • < DEC < 36 • , in the right ascension intervals of 21 h 30 m < RA < 3 h 15 m (South galactic hemisphere) and 7 h 20 m < RA < 16 h 40 m (North galactic hemisphere).…”
Section: Log-normal Simulated Cataloguesmentioning
confidence: 99%
“…Measurements resulting from some earlier studies already suggested a large bulk flow (Rubin et al 1976;Lynden-Bell et al 1988). More recently, reports in the literature (see, e.g., Mc Conville & Colgáin 2023;Hong et al 2014;Kalbouneh et al 2023;Perivolaropoulos 2023) have studied the magnitude and direction of this bulk flow velocity with diverse approaches and investigating various cosmic tracers, where these studies confirm the dipole nature of the bulk flow, but point out some differences in the velocity magnitude and/or direction (Turnbull et al 2012;Scrimgeour et al 2016;Qin et al 2018;Avila et al 2023;Watkins et al 2023;Whitford et al 2023).…”
Section: Introductionmentioning
confidence: 98%
“…An improved cosmological model-independent method of determining the value of the Hubble constant was also recently proposed by [40]. The determination of H 0 by methods with minimal cosmological assumptions has been recently developed in the literature by several authors [41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%